2016
DOI: 10.1016/j.dci.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

B cells and their role in the teleost gut

Abstract: Mucosal surfaces are the main route of entry for pathogens in all living organisms. In the case of teleost fish, mucosal surfaces cover the vast majority of the animal. As these surfaces are in constant contact with the environment, fish are perpetually exposed to a vast number of pathogens. Despite the potential prevalence and variety of pathogens, mucosal surfaces are primarily populated by commensal non-pathogenic bacteria. Indeed, a fine balance between these two populations of microorganisms is crucial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 194 publications
(357 reference statements)
1
53
0
Order By: Relevance
“…Teleost B-cells exhibit additional phagocytic and microbicidal functions not typically seen in higher vertebrates (Li et al, 2006;Øverland, Pettersen, Rønneseth, & Wergeland, 2010), and they can also function as initiating antigen-presenting cells, linking the innate and adaptive immune systems in zebrafish (Lewis, Del Cid, & Traver, 2014;Zhu et al, 2014). In teleosts, intestinal mucosal immunity is largely dependent on B-cells acting as the primary responders to perturbation, but our understanding of their origins and full spectrum of functions in maintaining gut homeostasis is still limited (see Parra, Korytář, Takizawa, & Sunyer, 2016 for review). Immersion infection can be used for larvae beginning when the mouth first opens at around 3 dpf (Ng et al, 2005).…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
“…Teleost B-cells exhibit additional phagocytic and microbicidal functions not typically seen in higher vertebrates (Li et al, 2006;Øverland, Pettersen, Rønneseth, & Wergeland, 2010), and they can also function as initiating antigen-presenting cells, linking the innate and adaptive immune systems in zebrafish (Lewis, Del Cid, & Traver, 2014;Zhu et al, 2014). In teleosts, intestinal mucosal immunity is largely dependent on B-cells acting as the primary responders to perturbation, but our understanding of their origins and full spectrum of functions in maintaining gut homeostasis is still limited (see Parra, Korytář, Takizawa, & Sunyer, 2016 for review). Immersion infection can be used for larvae beginning when the mouth first opens at around 3 dpf (Ng et al, 2005).…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
“…The intestinal mucosa serves as the first line of host defence against inflammation and pathogen infection, especially in fish, which live in a pathogen-rich aquatic environment (Chen et al 2015). Additionally, the intestinal epithelium can effectively prevent the translocation of gut pathogens and their toxins into systemic circulation (Deitch 2002;Rombout et al 2011;Parra et al 2016). In mammals, many studies have shown that pathogens can alter the intestinal barrier function, induce an inflammatory response promote intestinal mucosal epithelium cell damage and apoptosis, and disrupt the tight junctions (TJs) and cytoskeleton (Mel et al 2000;Berkes et al 2003;Groschwitz and Hogan 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have used transcript analysis to define the responses occurring in the gut post infection or oral vaccination [10,11,12]. A few have used immunohistochemistry, as with the identification and characterisation of IgT+ B cells that increase in number during parasite infection [13,14]. Further study of these leucocytes and their bioactivities, the molecules they express and secrete, and the way immune responses are established are needed to enable a better understanding of the immune response in the gut [3,15].…”
Section: Introductionmentioning
confidence: 99%